-7x – y = 0 7x + 8y = -6 What is the result of subtracting the second equation from the first?

Question

-7x – y = 0

7x + 8y = -6

What is the result of subtracting the second equation from the first?

in progress 0
Skylar 2 weeks 2021-11-18T13:23:44+00:00 1 Answer 0 views 0

Answers ( )

    0
    2021-11-18T13:24:53+00:00

    Answer:

    -14x – 9y = 6

    Step-by-step explanation:

    subtract the similar terms from each other

    -7x – 7x = -14x

    -y – 8y = -9y

    0 – – 6 = 0 + 6 = 6

    put it together:

    -14x – 9y = 6

    hope this helps

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )